Relationship between agility and selected performance variables in male A-division rugby players in Gaborone, Botswana - Mosimakoko, K.; Onyewadum, I. U. (African Journal for Physical Activity and Health Sciences, 2021)
The purpose of this study was to analyse the relationships between agility and hip joint flexibility, muscle mass and anaerobic power in male A-division rugby players in Gaborone, Botswana. Simple random sampling technique was used to select eighty players from four A-division rugby teams in Gaborone. Testing took place over a three-day period in the morning. On the first day, body mass, agility (Illinois agility test) and flexibility (Sit and reach test) were measured. Skinfold measurements were taken on the second day and the Wingate anaerobic test was undertaken on the third day. All measurements were taken at the University of Botswana`s Exercise Physiology Laboratory, the University of Botswana stadium, and the gymnasium of the Botswana Defence Force. Pearson`s product-moment correlation coefficients were computed to examine the relationships between agility and the physical variables. The players` agility was not significantly related to hip flexibility (r = .030; p= 0.789) and fatigue index (r = .063; p= 0.577). Conversely, agility was significantly related to fat-free muscle mass (r = .355; p= .001), anaerobic peak power (r = .229; p = .041), and average anaerobic power (r = .257, p = .021). The findings implicate the need for physical trainers and coaches to encourage players to increase fat-free muscle mass, anaerobic peak power, and average anaerobic power to improve their performances in skills requiring agility. Also, coaching programmes should be designed to emphasise the development of these attributes in rugby players.